(untitled) (Eurasian Journal of Humanities and Social Sciences, 2023)
This article focuses on the investigation of nominative processes and lexical changes happening at the current stage of English language development. The processes of social, cultural, scientific, and political life, all imply ongoing linguistic evolution. When new linguistic units first develop, linguistic and extra linguistic variables both have a big impact. In our country the main signs of new words, their semantic structure, structural and classification of semantic types, lexical-grammatical-syntactic of components the properties have been extensively and thoroughly studied. New in scientific and technical texts words are of particular interest not only in content, but also in form. The purpose of this work is some lexical-semantic of neologisms in the current English Dictionary is the research of properties. In this case, the following tasks are solved: - research of the semantic characteristics of neologisms; - description of the lexical features of neologisms; - factors of development of neologisms into the vocabulary of the English language identify